Thermally Stable Monoruthenium Acetylide Radical Species - Tanaka, Yuya; Yashiro, Atsushi; Akita, Munetaka (Synlett, 2024)
Control of radical reactivity is regarded as an important concern in the fields of catalysis and materials sciences. Radical species generated from monoruthenium acetylide complexes are, in general, highly reactive, and therefore structural characterization of these species has remained elusive. In this paper, a spectroscopic and structural characterization of the cationic radical species of a monoruthenium diacetylide bearing a Ru tetraphosphine fragment, [trans-(Ar–SC≡C)2Ru(dppe)2]SbCl6 ([1]+SbCl6) [Ar: p-t-BuC6H4; dppe: 1,2-bis(diphenylphosphino)ethane], is presented. The formation of the radical species [1]+ is supported by the vis-NIR, IR, and ESR studies. Furthermore, the solid-state structure of [1]+ reveals a significant contribution of the cumulenic Ru=C=C=S resonance structure. Remarkably, the thermal stability of [1]+ results from the incorporation of the electron-donating (arylsulfanyl)ethynyl ligands and the highly sterically demanding dppe ligands as compared with a monoruthenium complex with less-bulky and less-electron-rich derivatives.
Keywords: radicals; stable radicals; metal acetylides; ruthenium complexes; ESR; X-ray crystallography